Platelet derived growth factor and fibroblast growth factor basic levels in the vitreous of patients with vitreoretinal disorders. Issue 2 (1st February 1998) - Cassidy, L; Barry, P; Shaw, C; Duffy, M J; Kennedy, S
Abstract : AIM: To determine the potential role of basic fibroblast growth factor (bFGF) and platelet derived growth factor (PDGF) in the pathogenesis of proliferative vitreoretinopathy (PVR). METHODS: An enzyme linked immunosorbent assay technique was used to determine the quantities of bFGF and PDGF in 38 vitreous samples taken from patients undergoing trans pars plana vitrectomy (PPV) for a variety of vitreoretinal disorders. RESULTS: bFGF levels ranged from undetectable to 318.7 pg/ml. The mean concentration was 27.57 pg/ml. PDGF levels ranged from undetectable to 160 pg/ml, the mean concentration being 40.06 pg/ml. Eight of 13 patients with clinical evidence of retinal detachment (RD) and PVR had significantly elevated bFGF concentrations, whereas only one of 11 patients with RD and no PVR had detectable bFGF; seven of eight patients with RD and PVR had elevated PDGF concentrations in the vitreous, whereas all 10 patients with RD and no PVR had no detectable vitreous PDGF. Eight patients with vitreous haemorrhage had raised PDGF concentrations, and the levels were particularly high (>120 pg/ml) in those two patients with active neovascularisation. Two out of nine patients with vitreous haemorrhage had raised bFGF levels. CONCLUSIONS: bFGF and PDGF concentrations are elevated in PVR even in the absence of vitreous haemorrhage, and not in patients with RD uncomplicated by PVR. This observation suggests that both cytokines may be involved in the pathogenesis of PVR.